The Role Of Human Capital In Economic Growth In Syria - موسى نرمين; عامر وليد; صيوح لؤي (Latakia University Journal - Economic and Legal Sciences Series, 2020)
The aim of this study to discover the role of the human capital in economic growth in Syria and work to develop and achieve this role. The study depended on econometric technical (IT,VECM) to clear relationship Between human capital and economic growth in Syria, we used E-views 9 to Achieve the role of this study. The most important results of this study, there are a balanced relationship between Enrollment rate(primary, secondary, tertiary) and economic growth in short term and long term, and we found a balanced relationship between public expenditure rates on education as( a rate of GDP) and economic growth during the period of study.